Harmonizing Services for Inclusive Growth : Improving Access to Essential Services for Vulnerable Groups in Bulgaria - World Bank (World Bank, Washington, DC, 2019)
European countries increasingly focus on enhancing access to and strengthening explicit linkages between benefits and essential services to create synergies, avoid dependency of low income families on allowances, and promote labor market participation of the inactive and vulnerable population. In order to facilitate access to support people need, Member States are advised to work on better coordination of social benefits and services to reduce poverty and support social and labor integration. This report defines essential services as education, health, and social, child protection and employment services, and social benefits as non-contributory cash allowances. Available evidence suggests that there is substantial scope to improve the effectiveness of essential services and benefits in Bulgaria, and that only partial coverage of vulnerable groups and limited progress in poverty reduction have been achieved. The system has substantial quantity and quality gaps in coverage, especially for the bottom 20 percent of the population. The essential services and benefits provide unbalanced responses to different vulnerabilities, and are particularly unsuccessful in offering the poor population an adequate level of support.